Berry Convenient: Online Design Preferences for Local Strawberries - Rachel Corry; Jessica Holt; Alexa J. Lamm; Abigail Borron (Journal of Applied Communications, 2023)
Agricultural marketers and grocery retailers are tasked with developing effective online marketing of local food products as consumer purchasing preferences shift. Local food sales are increasing through intermediated channels including grocery stores, and consumers are turning to online grocery shopping for their food purchases. Exploration of consumer preferences for visual and textual elements of an online local food product can provide marketing practitioners with strategies to optimize the purchase intent for local food among diverse audiences. Consumers are demonstrating interest in sustainability and information about food production, yet limited research has applied these interests to explore preferences for how local food is presented online. The purpose of this study was to explore consumer preferences for an online grocery design displaying local strawberries, and their purchase intention for local strawberries after viewing one of three designs. An online survey of 906 respondents from Florida, Georgia, and Alabama was used to collect data. Findings revealed that most individuals (42.9%, n = 389) prefer the online design with added information about environmental impact measures associated with local strawberries. However, there were demographic differences in preferred attributes of an online grocery design, and purchase intent was similar for local strawberries regardless of the design. Agricultural marketers should incorporate audience segmentation principles when customizing online grocery platforms for different individuals. Consumers should be presented with their preferred online design according to influential demographic variables and the type of grocery market providing the product. Additional recommendations for agricultural marketers and grocery retailers are provided.
Keywords: Local food; online grocery shopping; consumer purchasing; visual design; marketing